2019
DOI: 10.1002/jmv.25645
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical features of rotavirus, adenovirus, and astrovirus infections and coinfections in children with acute gastroenteritis prior to rotavirus vaccine introduction in Meerut, North India

Abstract: There are limited reports on the etiology of multiple enteric viruses causing acute gastroenteritis (AGE) in North India. In the present study we have determined the prevalence of three enteric viruses, namely rotavirus, astrovirus (AstV) and adenovirus (AdV) in a total of 312 diarrheic children (<5 years) hospitalized at Lala Lajpat Rai Memorial Medical College, Meerut, Uttar Pradesh from August 2014 to July 2016; and results were compared with data from Delhi. The fecal samples were individually screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
6
9
1
Order By: Relevance
“…The present data showed that there was a high percentage (37.4 %) of co-infection in this study among HAdV-F-positive samples. The results obtained here were consistent with those of previous studies, which have reported worldwide occurrence rates of viral co-infections ranging from 8.0-44.8 % [12,72,[76][77][78][79][80]. The most common co-infection obtained was a dual infection with HAdV-F and RVA, with a detection rate of 21.5 %, in contrast to reports from India (16.1%) [80], France (16 %) [81], Nigeria (5.9 %) [72] and previous studies conducted in Brazil (8.3 %) [21] with lower detection rates.…”
Section: Discussionsupporting
confidence: 93%
“…The present data showed that there was a high percentage (37.4 %) of co-infection in this study among HAdV-F-positive samples. The results obtained here were consistent with those of previous studies, which have reported worldwide occurrence rates of viral co-infections ranging from 8.0-44.8 % [12,72,[76][77][78][79][80]. The most common co-infection obtained was a dual infection with HAdV-F and RVA, with a detection rate of 21.5 %, in contrast to reports from India (16.1%) [80], France (16 %) [81], Nigeria (5.9 %) [72] and previous studies conducted in Brazil (8.3 %) [21] with lower detection rates.…”
Section: Discussionsupporting
confidence: 93%
“…This result matches recent reports in the Republic of Congo (10.3%) 13 and India (12.5%). 14 However, our finding is higher than previous results in Kenya (6.3%), 15 Northwest Ethiopia (3.6%), 8 lower than others obtained in Egypt by El Taweel et al (2020): 28%, 16 and Nigeria: 40.4%. 17 The higher prevalence obtained in Egypt may be due to the inclusion of novel human astrovirus types.…”
Section: Discussioncontrasting
confidence: 77%
“…Astrovirus diarrhea is a common infection both in developed and developing countries, which suggests that the improvement of the hygiene and living conditions alone cannot prevent such infection. 8,[13][14][15][16][17][18] Development of an astrovirus vaccine and its administration in early life may have a role in reducing this infection in early life and even decrease the incidence of astrovirus diarrhea with increasing age. 19 Regarding the clinical features associated with diarrhea in HAstV positive patients, the degrees of dehydration (mild, moderate, and severe) were detected in astrovirus positive cases with no significant association of classic HAstV with any of them (p=0.463).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human Astroviruses (HAstVs; family Astroviridae) are common aetiological agents of acute paediatric gastroenteritis, after rotavirus and the caliciviruses (Platts-Mills et al 2015;Vu et al 2017;Wohlgemuth et al 2019), and are detected at rates comparable to adenoviruses in cases of paediatric diarrhoea (Andreasi et al 2008;Levidiotou et al 2009;Hamkar et al 2010;Akdag et al 2020). HAstV-associated gastroenteritis is also reported in the adult population, particularly in the elderly and individuals with compromised immunity (Vu et al 2017;Wohlgemuth et al 2019).…”
Section: Astrovirusesmentioning
confidence: 99%